The Effects of Profitability, Leverage, and Liquidity on Financial Distress on Retail Companies Listed on Indonesian Stock Exchange - Neneng Susanti; Ifa Latifa; Denok Sunarsi (Program Pascasarjana Universitas Negeri Makassar, 2020)
The study aims to find out the influence of profitability variables (Return On Assets), Leverage (Debt To Asset Ratio) and liquidity (Current Ratio) on Financial Distress on retail companies listed on the 2014-2018 period Indonesian Stock Exchange. The population of this study is the entire company contained on the Indonesian Stock Exchange listed retail company of the period 2014-2018. The research sample consists of 21 companies used by purposive sampling methods and taken that meet with criteria from predetermined research samples. The data analysis method used is panel data regression analysis (Random Effect) with a significance level of 5 percent. Based on the results of the research that has been conducted led to that, simultaneously Profitability, Leverage and Liquidity variables have an effect on Financial Distress. Partially variable Profitability has a significant positive effect on Financial Distress, Leverage variables have a significant positive effect on Financial Distress, and negatively significant negatively influential Liquidity variables on Financial Distress. The magnitude of the influence of Profitability, Leverage, and Liquidity on Financial Distress amounted to 98.87 percent, while the rest amounted to 1.13 percent was affected by other variables outside of research.